Bone Graft Substitution and Augmentation. (December 2015) - Nauth, Aaron; Lane, Joseph; Watson, J. Tracy; Giannoudis, Peter
Abstract : Summary: Selection of appropriate bone graft or bone graft substitute requires careful recognition of the bone healing needs of the patient's specific clinical problem and a thorough understanding of the different properties possessed by the available bone grafts and substitutes. Although autogenous iliac crest bone graft remains the gold standard of treatment for delayed unions, nonunions, and bone defects, there are a number of promising alternatives available, and emerging evidence suggests that they can be very effective when used in the proper setting. Among these, reamer–irrigator–aspirator bone graft, bone marrow concentrate, bone morphogenetic proteins, and calcium phosphate cements have received a great deal of attention in the literature. This review describes these grafts in detail along with the evidence for their use. In addition, a framework is provided for selecting the appropriate graft or substitute based on their provided properties. Abstract : Supplemental Digital Content is Available in the Text.